2019
DOI: 10.1186/s12894-019-0441-0
|View full text |Cite
|
Sign up to set email alerts
|

Urethral cavernous hemangioma: a highly misdiagnosed disease (a case report of two patients and literature review)

Abstract: BackgroundDiagnosis of urethral cavernous hemangioma (UCH) is very rare. It can be easy to misdiagnose and mistreat due to its atypical clinical manifestations and a lack of relevant knowledge. The study is to explore the diagnosis, differential diagnosis, and treatment of UCH.Case presentationThe first patient was a 15-year-old male, who was admitted to the hospital for more than 1 year with repeated hematuria. UCH was diagnosed by cystoscope biopsy, and cured with local injection of pingyangmycin. The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Yong f et al [7] reported two cases of multiple treatments with hematuria, and finally diagnosed urethral cavernous hemangioma. At the same time, it also warned that sexual life may lead to rupture and bleeding of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Yong f et al [7] reported two cases of multiple treatments with hematuria, and finally diagnosed urethral cavernous hemangioma. At the same time, it also warned that sexual life may lead to rupture and bleeding of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…10 Fang et al reported that patients with urethral hemangioma in local hospital settings have received misdiagnoses such as seminal cystitis, urethritis, or prostatitis. 12 Urologists should bear in mind that the most common symptoms associated with urethral hemangioma include intermittent hematuria and, frequently, indolence. Additionally, it is essential to recognize the potential for hematuria to develop after erection and ejaculation.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of angiomas is limited because of the tissue of the urethral corpus cavernosum semi-encapsulated around the glans and corpus cavernosum of the penis and the relative depth of the penis. 2 Urethral Hemangioma usually has no obvious clinical manifestations. However, if it breaks through to the urethra, symptoms become apparent after erection or after ejaculation, making sarcoid hematuria the most important clinical feature of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Young men are more sexually active, so the disease is highly detectable but needs to be differentiated from vesiculitis. 2 In female patients, it is more often seen with the finding of urethral masses or vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation